The Neotropical genus Notodiaptomus Kiefer, 1936 (Calanoida: Diaptomidae): Redescription of the type species Notodiaptomus deitersi (Poppe, 1891) and designation of a neotype - Santos-Silva, Edinaldo Nelson (Studies on Neotropical Fauna and Environment, 2020)
Notodiaptomus Kiefer, 1936 is the most abundant and speciose genus of freshwater calanoids in the Neotropical region. The type species, N. deitersi (Poppe, 1891) is in need of redescription but the type material is no longer extant and the type locality no longer exists. In order to avoid possible confusion over the identity of the type species of the genus, a neotype is designated. This is an adult ♂ from Baia Pedra Branca because this locality is near Cuiaba, in the State of Mato Grosso, Brazil, the original type locality. The neotype is described and this description forms the basis for a complete diagnosis of the genus Notodiaptomus. Like most diaptomid genera Notodiaptomus is characterized by prosome morphology, by the fifth legs in both sexes and by the ♂ geniculate antennule. Sexual dimorphism in the rostrum is reported here and the homology of the modified setal elements on the geniculate right antennule of the ♂ is analysed.